ANALISIS KEPUTUSAN PEMBELIAN IPHONE APPLE YANG DILAKUKAN OLEH ORANG YANG TINGGAL DI JABODETABEK - Syarifah Zalicha; Nouval Ahmad; Patricia Gabriella D. A (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
This research is motivated by the rapid development of smartphones, where smartphones are one of the main needs of human activity. Apple is a company that competes vigorously with one of its products, the iPhone. This study aims to determine whether the Brand Image, Brand Loyalty and Perceived Value factors can determine iPhone purchasing decisions by consumers who live in Jabodetabek. The sampling method that this study will use is the quantitative methods in the form of surveys questionnaires for data collection using Convenience Sampling. The number of samples used in this study was 372 people in Jabodetabek who used the Apple iPhone to represent the entire population. The results of this study indicate that Brand Image does not have a significant and positive influence on purchasing decisions made by consumers in Jabodetabek. While other variables, namely Brand Loyalty and Perceived Value, have a significant and positive influence on purchasing decisions made by consumers in Jabodetabek.